Transport and Confinement in Bilayer Chiral Borophene - Albuhairan, Hassan (2021)
We employ a four-band continuum model to study the transport and confinement in an n-p-n junction in bilayer chiral borophene for both the identical- and oppositechirality configurations. The conditions for transport and confinement are elucidated in terms of the pseudospin. We study the transmission and reflection probabilities, conductances, and bound states. We demonstrate the existence of topological states in a domain wall between domains of opposite-chirality bilayer chiral borophene with reversed layer stacking. We find that changing the interlayer bias modifies the conductance of the identical-chirality configuration but not that of the opposite-chirality configuration, and that it induces a layer localization of the bound and topological states. Our findings suggest paths towards utilization of the layer degree of freedom in bilayer chiral borophene in future electronic devices.